Role of N-Linked Glycosylation in PKR2 Trafficking and Signaling - Verdinez, Jissele A.; Sebag, Julien A. (Frontiers in Neuroscience, 2021)
Prokineticin receptors are GPCRs involved in several physiological processes including the regulation of energy homeostasis, nociception and reproductive function. PKRs are inhibited by the endogenous accessory protein MRAP2 which prevents them from trafficking to the plasma membrane. Very little is known about the importance of post-translational modification of PKRs and their role in receptor trafficking and signaling. Here we identify 2 N-linked glycosylation sites within the N-terminal region of PKR2 and demonstrate that glycosylation of PKR2 at position 27 is important for its plasma membrane localization and signaling. Additionally, we show that glycosylation at position 7 results in a decrease in PKR2 signaling through Gs without impairing Gq/11 signaling.